Investigação sobre a influência das expectativas dos agentes econômicos em indicadores brasileiros - Freitas, Andreia Pereira de (2016)
The Brazilian economy adopts the regime of inflation targets since 1999 and one of the biggest challenges of monetary policy is to make the price takers form expectations and thus fix prices. Expectations guide the decisions of economic agents and are an important monetary policy transmission channel. Therefore, it is important that the monetary authority is transparent and has credibility with the public. An inflation target for a particular period is fully credible if it is equal to the inflation expectations of the market for the same period. This research aims to assess the way in which the expectations of economic agents influence the results in different economic indicators: Industrial Production, Exchange, Quarterly Agriculture GDP, Quarterly Industry GDP, Quarterly Service GDP, Quarterly Total GDP, IGPM, IPCA , Selic rate. The research analyzes how expectations affect the process of formation of own expectations and how the previous results influence the outcome of the next period and the formation of expectations. It uses the data of the statistical series available by Central Bank of Brazil of market expectations. The methodology is the time series and especially the Least Square Robust Models. We found the following results: For the Industrial Production and Exchange, previous expectations influenced the Last Expectation and the previous results were significant in the Result. For the IGP-M, only the previous results influenced the outcome, for the Last Expectation, all variables (previous expectations, previous results and deviations from previous expectations) were significant. For the IPCA and the Selic, all variables were statistically significant, the most relevant are short-term previous expectations, acting in the results and in the Last Expectation. For the Agriculture GDP, only previous expectations influenced the Last Expectation, and all variables had influence in the result. No variable searched for Industry GDP and Service GDP had an influence on the result. In Last Expectation, short-term expectations were significant. For the Total GDP, the previous expectations are significant in the result. Just previous expectations are significant in Average Last Expectation and only the expectation of two days before is significant in Median.